A kind of anti-swelling tough hydrogel and preparation method thereof

By constructing a hydrogel with a two-phase nanohybrid structure of hydrogel, the problem of swelling in the solvent is solved, its mechanical properties and adaptability are improved, and effective application in wet environments is achieved.

CN115368588BActive Publication Date: 2025-04-08SHENZHEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211128525.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-16
Publication Date
2025-04-08
Estimated Expiration
2042-09-16

AI Technical Summary

Technical Problem

Existing hydrogels are prone to swelling problems in solvents, resulting in significant attenuation of mechanical properties and poor adaptability, making them unable to be effectively applied in wet environments.

Method used

By blending hydrophilic organic polymer and silicone-based hydrophobic elastomer prepolymer, a hydrophilic two-phase nanohybrid structure was constructed, and combined with ultrasonic, refrigeration and dehydration treatment, an anti-swelling tough hydrogel was prepared.

Benefits of technology

The good mechanical deformation stability of the hydrogel and its swelling resistance underwater are achieved, enhancing its adaptability and application potential in wet environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115368588B_ABST
    Figure CN115368588B_ABST
Patent Text Reader

Abstract

The present invention discloses an anti-swelling tough hydrogel and a preparation method thereof, the preparation method comprising the steps of: adding a hydrophilic organic polymer to a solvent to obtain a first solution; mixing a liquid organosilicon-based hydrophobic elastomer prepolymer, the first solution, and a surfactant, and then ultrasonicating to obtain a second solution; cold-treating the second solution at a first preset temperature for a first preset time, and then placing it at room temperature for a second preset time to obtain a hydrogel precursor; and dehydrating the hydrogel precursor to obtain an anti-swelling tough hydrogel. The present invention constructs a unique hydrophilic and hydrophobic two-phase nano-hybrid structure by blending a hydrophilic organic polymer and an organosilicon-based hydrophobic elastomer prepolymer. The introduction of the hydrophilic organic polymer enables the anti-swelling tough hydrogel to have good mechanical deformation stability, and the introduction of the organosilicon-based hydrophobic elastomer improves the elasticity and underwater anti-swelling performance of the anti-swelling tough hydrogel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogels, and in particular to an anti-swelling tough hydrogel and a preparation method thereof. Background Art

[0002] Similar to biological tissues, hydrogels are continuous colloid or polymer network structure materials containing a large amount of water, and their water content can even exceed 95% (mass fraction). However, compared with biological tissues, the application of hydrogels still faces many challenges: first, the mechanical properties of hydrogels are far from those of biological soft tissues, and the mechanical characteristics of conventional synthetic hydrogels are soft and brittle; second, biological tissues are immersed in tissue fluids for a long time and have high stability, while hydrogels will swell in solvents (such as water), causing their mechanical properties to significantly decay and hydrogels to have poor adaptability.

[0003] Hydrogel swelling is the phenomenon that the cross-linked network formed by the polymer absorbs the solvent in the aqueous solution due to the solvation of the polymer chains, resulting in volume expansion. This process can often expand to a considerable extent. When in contact with water, the gel will absorb water, and the water can diffuse into the polymer network, but the polymer chains in the network cannot diffuse out. When the internal pressure of the stretched gel network is equal to the osmotic pressure, the swelling stops. The swelling of hydrogel materials will cause a significant increase in the volume of the material and at the same time cause the attenuation of its mechanical properties, thus limiting the application of hydrogels in wet environments.

[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide an anti-swelling tough hydrogel and a preparation method thereof, aiming to solve the problem that the existing hydrogel has poor anti-swelling performance and cannot be used in the environment.

[0006] The technical solution of the present invention is as follows:

[0007] The first aspect of the present invention provides a method for preparing an anti-swelling tough hydrogel, which comprises the steps of:

[0008] Providing a liquid silicone-based hydrophobic elastomer prepolymer, a hydrophilic organic polymer and a surfactant; adding the hydrophilic organic polymer to a solvent to obtain a first solution;

[0009] After mixing the liquid organosilicon-based hydrophobic elastomer prepolymer, the first solution, and the surfactant, ultrasonically performing the mixture to obtain a second solution;

[0010] The second solution is cooled at a first preset temperature for a first preset time, and then placed at room temperature for a second preset time to obtain a hydrogel precursor;

[0011] The anti-swelling tough hydrogel is obtained by dehydrating the hydrogel precursor.

[0012] Optionally, the hydrophilic organic polymer includes polyvinyl alcohol, the liquid silicone-based hydrophobic elastomer prepolymer includes polydimethylsiloxane prepolymer, and the surfactant includes Tween 80.

[0013] Optionally, the mass ratio of the hydrophilic organic polymer, the liquid silicone-based hydrophobic elastomer prepolymer, and the surfactant is 1:(0.25-9):0.08.

[0014] Optionally, the solvent is selected from water or an aqueous solution of a water-soluble organic solvent.

[0015] Optionally, the water-soluble organic solvent in the water-soluble organic solvent aqueous solution is selected from at least one of glycerol and ethylene glycol.

[0016] Optionally, the first preset temperature is -20°C to -70°C, the first preset time is at least 2 days, and the second preset time is at least 2 days.

[0017] Optionally, the step of dehydrating the hydrogel precursor comprises:

[0018] The hydrogel precursor is placed at a temperature of 30-40° C. for at least 2 days, and then placed at a temperature of 60-80° C. for dehydration.

[0019] Optionally, after dehydrating the hydrogel precursor and before obtaining the anti-swelling tough hydrogel, the method further comprises the following steps:

[0020] The dehydrated product is immersed in an ionic liquid solution and / or a salt solution.

[0021] Optionally, after dehydrating the hydrogel precursor and before obtaining the anti-swelling tough hydrogel, the method further comprises the following steps:

[0022] The metal layer is deposited on the surface of the dehydrated product by electroless deposition.

[0023] The second aspect of the present invention provides an anti-swelling tough hydrogel, wherein the hydrogel is prepared by the preparation method of the present invention as described above.

[0024] Beneficial effects: The present invention constructs a unique hydrophilic and hydrophobic two-phase nano-hybrid structure by blending a hydrophilic organic polymer and a silicone-based hydrophobic elastomer prepolymer, which combines the flexible stretching of the hydrophilic organic polymer and the elastic advantages of the silicone-based hydrophobic elastomer. The introduction of the hydrophilic organic polymer enables the anti-swelling tough hydrogel to have good mechanical deformation stability, while the introduction of the silicone-based hydrophobic elastomer improves the elasticity and underwater anti-swelling performance of the anti-swelling tough hydrogel. In the anti-swelling tough hydrogel, the interpenetrating hydrophilic organic polymer serves as a gel matrix, and the interpenetrating hydrophilic organic polymer matrix serves as a binder to assemble the silicone-based hydrophobic elastomer microspheres, in which the densely packed silicone-based hydrophobic elastomer microspheres are dispersed. The densely packed silicone-based hydrophobic elastomer microspheres provide its mechanical toughness and inhibit water penetration; the hydrophilic organic polymer is easily solvated and acts as a water channel. With the assistance of this hydrophilic and hydrophobic two-phase component, the water content can be easily regulated, so that the hydrogel has good anti-swelling performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The figure is a schematic diagram of the preparation process of the anti-swelling tough hydrogel in an embodiment of the present invention.

[0026] Figure 2 (a) is a graph showing the anti-swelling performance of the anti-swelling tough hydrogel in Example 1 of the present invention after being immersed in water for different periods of time, and (b) is a comparison graph showing the volume change ratio of the anti-swelling tough hydrogel in Example 1 of the present invention after being immersed in water for one day.

[0027] Figure 3 This is a visual diagram of the anti-swelling performance of the anti-swelling tough hydrogel in Example 1 of the present invention after being immersed in water for different days.

[0028] Figure 4 This is a curve diagram of the mass and diameter changes of the anti-swelling tough hydrogel in Example 1 of the present invention after being immersed in water for different days.

[0029] Figure 5 (a)-(d) are the flexibility test results of the anti-swelling tough hydrogel with ion conductivity at -60°C obtained by immersing the anti-swelling tough hydrogel in a dry state in lithium chloride solution, potassium chloride solution, BMIMBF4 solution, and LiTFSI solution in Example 2, respectively.

[0030] Figure 6 The graphs show the results of the conductivity test of the anti-swelling tough hydrogel with ionic conductivity obtained by immersing the anti-swelling tough hydrogel in a dry state in a lithium chloride solution at a temperature of -40°C in Example 2 of the present invention, wherein (a) is the result without power supply, and (b) is the result with power supply.

[0031] Figure 7 This is a graph showing the flexibility test results of the anti-swelling tough hydrogel with a metal nickel layer on its surface prepared in Example 3 of the present invention.

[0032] Figure 8 (a) is a surface SEM image of the anti-swelling tough hydrogel with a metal nickel layer on its surface prepared in Example 3, and (b) is a cross-sectional SEM image of the anti-swelling tough hydrogel with a metal nickel layer on its surface prepared in Example 3.

[0033] Fig. 9 This is a graph showing the conductivity test results of the anti-swelling tough hydrogel with a metal nickel layer on the surface prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0034] The present invention provides an anti-swelling tough hydrogel and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0035] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0036] Compared with biological tissues, the application of hydrogels still faces many challenges: First, the mechanical properties of hydrogels are far from those of biological soft tissues, and the mechanical characteristics of conventional synthetic hydrogels are soft and brittle; second, biological tissues are immersed in tissue fluids for a long time and have high stability, while hydrogels will swell in solvents (such as water), causing their mechanical properties to significantly decay and hydrogels to have poor adaptability. In order to achieve the performance of biological soft tissues, improve the toughness, elasticity and environmental adaptability of hydrogels, and improve the comprehensive performance of hydrogels, the embodiments of the present invention provide a method for preparing anti-swelling tough hydrogels, such as Figure 1 As shown, the steps include:

[0037] S1. providing a liquid silicone-based hydrophobic elastomer prepolymer, a hydrophilic organic polymer and a surfactant;

[0038] S2, adding the hydrophilic organic polymer into a solvent to obtain a first solution;

[0039] S3, mixing the liquid organosilicon-based hydrophobic elastomer prepolymer, the first solution, and the surfactant, and performing ultrasound to obtain a second solution;

[0040] S4, cooling the second solution at a first preset temperature for a first preset time, and then placing it at room temperature for a second preset time to obtain a hydrogel precursor;

[0041] S5, dehydrating the hydrogel precursor to obtain the anti-swelling tough hydrogel.

[0042] In an embodiment of the present invention, a liquid silicone-based hydrophobic elastomer prepolymer is used to help the initial shaping of the gel structure. Then, the hydrophilic polymer gel is frozen and thawed, which helps to uniformly pre-fix the hydrophobic elastomer pre-crosslinked microspheres in the gel and form the hydrogel. Specifically, the second solution is placed at a first preset temperature for a first preset time and then placed at room temperature to achieve freeze-thaw of the hydrophilic organic polymer gel. Further, during the second preset time at room temperature, the silicone-based hydrophobic elastomer is completely polymerized to obtain a gel precursor. Finally, the hydrophilic organic polymer inside the gel precursor is slowly dehydrated and crystallized to form hydrophilic polymer nanocrystals, and then dehydrated at high temperature to obtain an anti-swelling tough hydrogel in a dry state.

[0043] The embodiment of the present invention constructs a unique hydrophilic and hydrophobic two-phase nano-hybrid structure by blending a hydrophilic organic polymer and a silicone-based hydrophobic elastomer prepolymer, combining the flexible stretching of the hydrophilic organic polymer and the elastic advantages of the silicone-based hydrophobic elastomer, and for the first time realizes the preparation of a silicone-based tough hydrogel with good anti-swelling ability. Among them, the introduction of the hydrophilic organic polymer makes the anti-swelling tough hydrogel have good mechanical deformation stability, while the introduction of the silicone-based hydrophobic elastomer improves the elasticity and underwater anti-swelling performance of the anti-swelling tough hydrogel. In the anti-swelling tough hydrogel, the interpenetrating hydrophilic organic polymer serves as a gel matrix, and the interpenetrating hydrophilic organic polymer matrix serves as a binder to assemble silicone-based hydrophobic elastomer microspheres, and the densely packed silicone-based hydrophobic elastomer microspheres are dispersed therein. The densely packed silicone-based hydrophobic elastomer microspheres provide mechanical toughness and inhibit water penetration; the hydrophilic organic polymer is easily solvated and acts as a water channel. With the help of this hydrophilic and hydrophobic two-phase component, the water content can be easily regulated, so that the hydrogel has good anti-swelling properties. The formation of hydrophilic polymer nanocrystals significantly improves the interface bonding of the organosilicon-based hydrophobic elastomer microspheres on the hydrophilic organic polymer matrix, and improves the strength of the interface between the organosilicon-based hydrophobic elastomer microspheres and the hydrophilic organic polymer matrix. In addition, the formation of hydrophilic organic polymer nanocrystals also prevents the solvation of the hydrophilic organic polymer matrix (strong hydrogen bonds), promoting the stability of the anti-swelling tough hydrogel.

[0044] Compared with the preparation method of traditional polymer hydrogels such as multi-network cross-linked hydrogels by chemical cross-linking, the method provided in this embodiment can effectively avoid the toxicity problem of unreacted monomers and initiators.

[0045] In step S1, in one embodiment, the method for preparing the liquid silicone-based hydrophobic elastomer prepolymer comprises the steps of:

[0046] After the hydrogenated silicone-based hydrophobic elastomer is mixed with the cross-linking agent, a liquid silicone-based hydrophobic elastomer prepolymer is obtained.

[0047] In one embodiment, the liquid silicone-based hydrophobic elastomer prepolymer includes but is not limited to polydimethylsiloxane (PDMS) prepolymer.

[0048] In one embodiment, the hydrogenated silicone-based hydrophobic elastomer includes but is not limited to hydrogenated polydimethylsiloxane (PDMS), and the structural formula of hydrogenated PDMS is n can be any integer greater than or equal to 1.

[0049] In one embodiment, the crosslinking agent is not limited to vinyl siloxane, and the structural formula of vinyl siloxane is n can be any integer greater than or equal to 1.

[0050] In step S2, in one embodiment, the hydrophilic organic polymer includes but is not limited to polyvinyl alcohol (PVA).

[0051] In one embodiment, the solvent is selected from water or a water-soluble organic solvent aqueous solution. The water-soluble organic solvent aqueous solution is prepared by dissolving a water-soluble organic solvent in water.

[0052] In one embodiment, the mass fraction of the water-soluble organic solvent in the water-soluble organic solvent aqueous solution is 30-90%, for example, it can be 30%, 40%, 50%, 60%, 70%, 80% or 90%.

[0053] In one embodiment, the water-soluble organic solvent in the water-soluble organic solvent aqueous solution is selected from at least one of glycerol and ethylene glycol. When a water-soluble organic solvent is used, the mechanical properties of the hydrogel can be improved.

[0054] In step S3, in one embodiment, the mass ratio of the hydrophilic organic polymer, the liquid silicone-based hydrophobic elastomer prepolymer, and the surfactant is 1: (0.25-9): 0.08. For example, the mass ratio of the hydrophilic organic polymer, the liquid silicone-based hydrophobic elastomer prepolymer, and the surfactant can be 1: 0.25: 0.08, 1: 1: 0.08, 1: 2: 0.08, 1: 3: 0.08, 1: 5: 0.08, 1: 7: 0.08, 1: 9: 0.08, etc.

[0055] In step S3, in one embodiment, the surfactant includes but is not limited to Tween 80.

[0056] In step S4, the second solution is placed at a first preset temperature for a first preset time after being cold-treated, and then placed at room temperature for a second preset time to obtain a hydrogel precursor. In step S1, the organosilicon-based hydrophobic elastomer microspheres have been pre-crosslinked to help the initial shaping of the gel structure, and in this process, the hydrophilic polymer gel undergoes freeze-thaw, which helps the organosilicon-based hydrophobic elastomer pre-crosslinked microspheres to be uniformly pre-fixed in the gel and allows the hydrogel to be formed. Specifically, the second solution is placed at a first preset temperature for a first preset time after being cold-treated, and then placed at room temperature to achieve freeze-thaw of the hydrophilic organic polymer gel. Further, during the process of standing at room temperature for the second preset time, the organosilicon-based hydrophobic elastomer is completely polymerized.

[0057] In one embodiment, the first preset temperature is -20°C to -70°C, the first preset time is at least 2 days, and the second preset time is at least 2 days. The hydrophilic organic polymer gel can be fully frozen and thawed by cooling at a temperature of -20°C to -70°C for at least 2 days and then thawing at room temperature. Then, the hydrophilic organic polymer gel can be allowed to stand at room temperature for at least 2 days to completely polymerize the silicone-based hydrophobic elastomer.

[0058] In step S5, in one embodiment, the step of dehydrating the hydrogel precursor comprises:

[0059] The hydrogel precursor is placed at a temperature of 30 to 40°C for at least 2 days, and then placed at a temperature of 60 to 80°C for dehydration. During the process of placing the hydrogel precursor at a temperature of 30 to 40°C for at least 2 days, the hydrophilic organic polymer inside the gel precursor slowly dehydrates and crystallizes to form hydrophilic polymer nanocrystals, and then dehydrates at a high temperature of 60 to 80°C to obtain an anti-swelling tough hydrogel in a dry state. The formation of hydrophilic polymer nanocrystals significantly improves the interface bonding of the organosilicon-based hydrophobic elastomer microspheres on the hydrophilic organic polymer matrix, and improves the strength of the interface between the organosilicon-based hydrophobic elastomer microspheres and the hydrophilic organic polymer matrix. In addition, the formation of hydrophilic organic polymer nanocrystals also prevents the solvation of the hydrophilic organic polymer matrix (strong hydrogen bonds), and promotes the stability of the anti-swelling tough hydrogel.

[0060] In this embodiment, the time for dehydration at a temperature of 60 to 80° C. can be selected according to actual needs and is not specifically limited here.

[0061] In order to further improve the adaptability and applicability of the anti-swelling tough hydrogel, so that it can be used in all-weather electronic skin, smart sensors in solvents, and soft robots in various harsh liquid environments, the product after the above dehydration treatment can be further processed. In one embodiment, after the hydrogel precursor is dehydrated, before obtaining the anti-swelling tough hydrogel, the following steps are also included:

[0062] S51, soaking the dehydrated product in an ionic liquid solution and / or a salt solution. This step obtains an anti-swelling tough hydrogel with ionic conductivity. The soaking time can be set according to actual needs, for example, it can be 24 hours. In this embodiment, the dehydrated product can be soaked in an ionic liquid solution, the dehydrated product can be soaked in a salt solution, or the dehydrated product can be soaked in an ionic liquid solution and a salt solution.

[0063] In one embodiment, the ionic liquid in the ionic liquid solution is selected from at least one of 1-butyl-3-methylimidazolium tetrafluoroborate (BMIMBF4) and lithium bistrifluoromethanesulfonyl imide (LiTFSI), but is not limited thereto.

[0064] In one embodiment, the solvent in the ionic liquid solution is a glycerol aqueous solution. The content of glycerol in the glycerol aqueous solution can be set according to actual needs. For example, the mass fraction of glycerol in the glycerol aqueous solution can be 60%.

[0065] In one embodiment, the salt in the salt solution is selected from at least one of lithium chloride and potassium chloride, but is not limited thereto.

[0066] In one embodiment, the solvent in the salt solution is a glycerol aqueous solution. The content of glycerol in the glycerol aqueous solution can be set according to actual needs. For example, the mass fraction of glycerol in the glycerol aqueous solution can be 60%.

[0067] In one embodiment, after the hydrogel precursor is dehydrated, before the anti-swelling tough hydrogel is obtained, the process further comprises the following steps:

[0068] S52, using an electroless deposition method to deposit a metal layer on the surface of the dehydrated product. This step can obtain an anti-swelling tough hydrogel with electrical conductivity underwater.

[0069] In a further embodiment, the step of depositing a metal layer on the surface of the dehydrated product by electroless deposition specifically comprises:

[0070] Mixing dopamine hydrochloride and tris(hydroxymethyl)aminomethane to prepare a third solution;

[0071] Soaking the dehydrated product in the third solution to prepare a polymer brush on the surface of the dehydrated product;

[0072] The dehydrated product with the polymer brush on its surface is immersed in a palladium catalyst solution, and then immersed in an electroless deposition metal salt solution, so that a metal layer is deposited on the surface of the dehydrated product.

[0073] According to the different components of the electroless deposition metal salt solution used, a metal nickel layer or a metal copper layer can be deposited on the surface of the product after the dehydration treatment.

[0074] The embodiment of the present invention further provides an anti-swelling tough hydrogel, wherein the hydrogel is prepared by the preparation method described above in the embodiment of the present invention.

[0075] The following describes it in detail through specific embodiments.

[0076] In the following examples, the raw materials used are all commercially available products, wherein the hydrogenated PDMS and vinyl siloxane used are purchased from Dow Corning, model SYLGARD184 (including hydrogenated PDMS and vinyl siloxane).

[0077] Example 1

[0078] Preparation of anti-swelling tough hydrogels with different PDMS addition amounts:

[0079] a. Mixing hydrogenated PDMS and vinyl siloxane in a mass ratio of 10:1, and mechanically stirring to obtain a PDMS prepolymer;

[0080] b. After mixing 1799 PVA with water, stir in a water bath at 90° C. for 1 hour to obtain a PVA solution with a PVA mass fraction of 10%;

[0081] c. According to the mass ratios of PDMS prepolymer, PVA and Tween 80 being 0:1:0.08, 0.25:1:0.08, 0.5:1:0.08, 1:1:0.08, 1.75:1:0.08, 3:1:0.08, 5:1:0.08 and 9:1:0.08 respectively, the PDMS prepolymer, PVA solution and Tween 80 were mixed, and then ultrasonicated by a cell crusher with the power set to 90% for 8 min and the program set to work for 2 s and rest for 2 s. After taking out, mix manually with a glass rod, and then ultrasonicate with a cell crusher for three cycles to obtain a uniformly dispersed mixed solution;

[0082] d. Pour the mixed solution into a mold, lay it flat and place it in a low-temperature box at -70°C for 2 days. After taking it out, place it at room temperature for 2 days to obtain a hydrogel precursor;

[0083] e. The hydrogel precursor was placed in an oven at 40°C for 2 days, and then placed in an oven at 60°C for dehydration to obtain an anti-swelling tough hydrogel in a dry state.

[0084] test:

[0085] (1) Under room temperature conditions, the anti-swelling properties of the obtained anti-swelling tough hydrogel after being immersed in water for different time periods are as follows: Figure 2 As shown in (a), the comparison of volume change ratio after soaking in water for one day is shown in Figure 2 As shown in (b). According to the mass ratios of PDMS prepolymer, PVA and Tween 80 being 0:1:0.08, 0.25:1:0.08, 0.5:1:0.08, 1:1:0.08, 1.75:1:0.08, 3:1:0.08, 5:1:0.08 and 9:1:0.08 respectively, the test results of the anti-swelling tough hydrogel prepared by mixing PDMS prepolymer, PVA solution and Tween 80 correspond to Figure 2 In (a), 0%, 20%, 33.3%, 50%, 66.7%, 75%, 83.3%, and 90% correspond to Figure 2 (b) PVA, 20%, 33.3%, 50%, 66.7%, 75%, 83.3%, 90%. It can be seen that the anti-swelling tough hydrogel has good anti-swelling performance.

[0086] (2) According to the mass ratio of PDMS prepolymer, PVA and Tween 80 being 3:1:0.08, the PDMS prepolymer, PVA solution and Tween 80 were mixed to finally prepare the anti-swelling tough hydrogel. The anti-swelling properties of the hydrogel were obtained by immersing it in water for different days. Figure 3 As shown, the mass and diameter change curves after being immersed in water for different days are as follows Figure 4 As shown, it can be seen that the mass and diameter do not change basically, and the anti-swelling tough hydrogel has good anti-swelling properties.

[0087] Example 2

[0088] (1) Preparation of anti-swelling tough hydrogel:

[0089] a. Mixing hydrogenated PDMS and vinyl siloxane in a mass ratio of 10:1, and mechanically stirring to obtain a PDMS prepolymer;

[0090] b. After mixing 1799 PVA with water, stir in a water bath at 90° C. for 1 hour to obtain a PVA solution with a PVA mass fraction of 10%;

[0091] c. According to the mass ratio of PDMS prepolymer, PVA and Tween 80 being 3:1:0.08, the PDMS prepolymer, PVA solution and Tween 80 were mixed, and then ultrasonicated using a cell crusher with the power set to 90% for 8 minutes and the program set to work for 2 seconds and rest for 2 seconds. After taking out, manually mix with a glass rod, and then ultrasonicate with a cell crusher for three cycles to obtain a uniformly dispersed mixed solution;

[0092] d. Pour the mixed solution into a mold, lay it flat and place it in a low-temperature box at -70°C for 2 days. After taking it out, place it at room temperature for 2 days to obtain a hydrogel precursor;

[0093] e. The hydrogel precursor was placed in an oven at 40°C for 2 days, and then placed in an oven at 60°C for dehydration to obtain an anti-swelling tough hydrogel in a dry state.

[0094] (2) Preparation of anti-swelling tough hydrogel with ionic conductivity:

[0095] a. Respectively mix lithium chloride, potassium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate (BMIMBF4), lithium bistrifluoromethanesulfonyl imide (LiTFSI) and glycerol aqueous solution (glycerol mass fraction is 60%) to prepare lithium chloride solution, potassium chloride solution, BMIMBF4 solution and LiTFSI solution with a concentration of 1 mol / L, respectively;

[0096] b. The anti-swelling tough hydrogel in the dry state in Example 2 was placed in the above four solutions and immersed for 24 hours respectively. After being taken out, an anti-swelling tough hydrogel with ion conductivity was obtained.

[0097] test:

[0098] (1) The flexibility test results of the ion-conductive, anti-swelling tough hydrogel prepared in Example 2 at -60°C are as follows: Figure 5 As shown in (a)-(d), it can be seen that after the anti-swelling tough hydrogel is placed in 1 mol / L lithium chloride solution, potassium chloride solution, BMIMBF4 solution, and LiTFSI solution, it still has good flexibility.

[0099] (2) The anti-swelling tough hydrogel with ion conductivity prepared in Example 2 (obtained by soaking in lithium chloride solution) was tested for conductivity at a temperature of -40°C. Figure 6 As shown in (a) and (b), the small light bulb is not lit when the power is not turned on (see Figure (a)), and the small light bulb is lit after the power is turned on (see Figure (b)), which proves that the anti-swelling tough hydrogel prepared in Example 2 has good conductivity.

[0100] Example 3

[0101] (1) Preparation of anti-swelling tough hydrogel:

[0102] a. Mixing hydrogenated PDMS and vinyl siloxane in a mass ratio of 10:1, and mechanically stirring to obtain a PDMS prepolymer;

[0103] b. After mixing 1799 PVA with water, stir in a water bath at 90° C. for 1 hour to obtain a PVA solution with a PVA mass fraction of 10%;

[0104] c. According to the mass ratio of PDMS prepolymer, PVA and Tween 80 being 3:1:0.08, the PDMS prepolymer, PVA solution and Tween 80 were mixed, and then ultrasonicated using a cell crusher with the power set to 90% for 8 minutes and the program set to work for 2 seconds and rest for 2 seconds. After taking out, manually mix with a glass rod, and then ultrasonicate with a cell crusher for three cycles to obtain a uniformly dispersed mixed solution;

[0105] d. Pour the mixed solution into a mold, lay it flat and place it in a low-temperature box at -70°C for 2 days. After taking it out, place it at room temperature for 2 days to obtain a hydrogel precursor;

[0106] e. The hydrogel precursor was placed in an oven at 40°C for 2 days, and then placed in an oven at 60°C for dehydration to obtain an anti-swelling tough hydrogel in a dry state.

[0107] (2) Preparation of anti-swelling tough hydrogel with a layer of metal nickel deposited on the surface:

[0108] 1) Preparation of polymer brushes:

[0109] a. Dopamine hydrochloride, tris(hydroxymethyl)aminomethane and water are mixed to obtain a mixed solution, wherein the mass fraction of dopamine hydrochloride is 0.2%, and the mass fraction of tris(hydroxymethyl)aminomethane is 0.12%.

[0110] b. Soaking the anti-swelling tough hydrogel in a dry state prepared in Example 3 in the above mixed solution for 12 hours to prepare a polymer brush on the surface of the anti-swelling tough hydrogel;

[0111] 2) Absorption of palladium catalyst:

[0112] a. Add tetrachloropalladium acid into water to prepare a tetrachloropalladium acid solution, wherein the mass fraction of tetrachloropalladium acid in the tetrachloropalladium acid solution is 0.1%.

[0113] b. Soaking the anti-swelling tough hydrogel containing the polymer brush on the surface in a tetrachloropalladium acid solution for 3 hours, so that the palladium catalyst is adsorbed on the surface of the polymer brush;

[0114] 3) Electroless deposition:

[0115] Table 1 Composition of liquid A and liquid B (solvent is water)

[0116]

[0117] a. Evenly mix solution A and solution B at a ratio of 1:1 (v / v) to obtain an electroless deposition solution;

[0118] b. Immerse the anti-swelling tough hydrogel containing palladium catalyst in an electroless deposition solution for 30 minutes to deposit a layer of metal nickel on the surface of the anti-swelling tough hydrogel.

[0119] test:

[0120] (1) The flexibility test results of the anti-swelling tough hydrogel containing a metal nickel layer on the surface prepared in Example 3 are as follows: Figure 7 As shown, it can be seen that it still has good flexibility.

[0121] (2) The surface and cross-sectional SEM images of the anti-swelling tough hydrogel containing a metal nickel layer prepared in Example 3 are as follows: Figure 8 As shown in (a) and (b).

[0122] (3) The conductivity test results of the anti-swelling tough hydrogel containing a metal nickel layer on the surface prepared in Example 3 are as follows: Fig. 9As shown, after being rubbed underwater, it still maintains good underwater conductivity (the small light bulb remains on).

[0123] In summary, the present invention provides an anti-swelling tough hydrogel and a preparation method thereof, wherein a hydrophilic organic polymer and a silicone-based hydrophobic elastomer are blended to construct a unique hydrophilic and hydrophobic two-phase nano-hybrid structure, which combines the flexible stretching of the hydrophilic organic polymer and the elastic advantages of the silicone-based hydrophobic elastomer. The introduction of the hydrophilic organic polymer enables the anti-swelling tough hydrogel to have good mechanical deformation stability, while the introduction of the silicone-based hydrophobic elastomer improves the elasticity and underwater anti-swelling performance of the anti-swelling tough hydrogel. In the anti-swelling tough hydrogel, the interpenetrating hydrophilic organic polymer is used as a gel matrix, and the interpenetrating hydrophilic organic polymer matrix is ​​used as a binder to assemble silicone-based hydrophobic elastomer microspheres, and the densely packed silicone-based hydrophobic elastomer microspheres are dispersed therein. The densely packed silicone-based hydrophobic elastomer microspheres provide mechanical toughness and inhibit water penetration; the hydrophilic organic polymer is easily solvated and acts as a water channel. With the assistance of this hydrophilic and hydrophobic two-phase component, the water content can be easily regulated, so that the hydrogel has good anti-swelling performance. In addition, post-treatment of the anti-swelling tough hydrogel can enable its application in all-weather electronic skin, smart sensors in solvents, and soft robots in various harsh liquid environments.

[0124] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing an anti-swelling tough hydrogel, characterized in that: Includes steps: Provide liquid silicone-based hydrophobic elastomer prepolymers, hydrophilic organic polymers and surfactants; adding the hydrophilic organic polymer into a solvent to obtain a first solution; After mixing the liquid organosilicon-based hydrophobic elastomer prepolymer, the first solution, and the surfactant, ultrasonically performing the mixture to obtain a second solution; The second solution is cooled at a first preset temperature for a first preset time, and then placed at room temperature for a second preset time to obtain a hydrogel precursor; The hydrogel precursor is subjected to a dehydration treatment to obtain the anti-swelling tough hydrogel; The first preset temperature is -20°C to -70°C, the first preset time is at least 2 days, and the second preset time is at least 2 days; The step of dehydrating the hydrogel precursor comprises: placing the hydrogel precursor at a temperature of 30-40°C for at least 2 days, and then placing it at a temperature of 60-80°C for dehydration; The anti-swelling tough hydrogel comprises a gel matrix and silicone-based elastomer microspheres dispersed in the gel matrix, wherein the gel matrix is ​​an interpenetrating hydrophilic organic polymer matrix; the interpenetrating hydrophilic organic polymer matrix is ​​used as a binder to assemble the silicone-based hydrophobic elastomer microspheres; The mass ratio of the hydrophilic organic polymer, the liquid silicone-based hydrophobic elastomer prepolymer, and the surfactant is 1: (0.25-9): 0.08; The hydrophilic organic polymer is polyvinyl alcohol, the liquid silicone-based hydrophobic elastomer prepolymer is polydimethylsiloxane prepolymer, and the surfactant is Tween 80.

2. The method for preparing the anti-swelling tough hydrogel according to claim 1, characterized in that: The solvent is selected from water or a water-soluble organic solvent aqueous solution.

3. The method for preparing the anti-swelling tough hydrogel according to claim 2, characterized in that: The water-soluble organic solvent in the water-soluble organic solvent aqueous solution is selected from at least one of glycerol and ethylene glycol.

4. The method for preparing the anti-swelling tough hydrogel according to claim 1, characterized in that: After the hydrogel precursor is subjected to dehydration treatment, the process further comprises the following steps before obtaining the anti-swelling tough hydrogel: The dehydrated product is immersed in an ionic liquid solution and / or a salt solution.

5. The method for preparing the anti-swelling tough hydrogel according to claim 1, characterized in that: After the hydrogel precursor is subjected to dehydration treatment, the process further comprises the following steps before obtaining the anti-swelling tough hydrogel: The metal layer is deposited on the surface of the dehydrated product by electroless deposition.

6. A swelling-resistant tough hydrogel, characterized in that: The preparation method is described in any one of claims 1 to 5.